2014
DOI: 10.1042/bj20140486
|View full text |Cite
|
Sign up to set email alerts
|

miR-21/DDAH1 pathway regulates pulmonary vascular responses to hypoxia

Abstract: The NOS (nitric oxide synthase) inhibitor ADMA (asymmetric dimethylarginine) contributes to the pathogenesis of pulmonary hypertension. Reduced levels of the enzymes metabolizing ADMA, dimethylarginine dimethylaminohydrolases (DDAH1 and DDAH2) and increased levels of miR-21 are linked to disease pathology, but the mechanisms are not understood. In the present study we assessed the potential role of miR-21 in the regulation of hypoxia-induced changes in ADMA metabolism in vitro and in vivo. Hypoxia inhibited DD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 46 publications
3
43
0
Order By: Relevance
“…These observations seem at odds with previous reports that have identified DDAH1 expression in a wide range of nonendothelial cell types, including vascular smooth muscle, renal, and neuronal cells. [18][19][20][21][22][23][24] To resolve this apparent discrepancy, we have independently generated an endothelium-specific DDAH1 −/− mouse. Using this model, we demonstrate endothelium-restricted expression of Cre activity that entirely removes DDAH1 protein in primary isolated endothelial cells.…”
mentioning
confidence: 99%
“…These observations seem at odds with previous reports that have identified DDAH1 expression in a wide range of nonendothelial cell types, including vascular smooth muscle, renal, and neuronal cells. [18][19][20][21][22][23][24] To resolve this apparent discrepancy, we have independently generated an endothelium-specific DDAH1 −/− mouse. Using this model, we demonstrate endothelium-restricted expression of Cre activity that entirely removes DDAH1 protein in primary isolated endothelial cells.…”
mentioning
confidence: 99%
“…Our first mathematical iteration identified miR-21 as controlling multiple PH target genes and pathways, including BMPR2 expression and hypoxic reprogramming, which we and others later validated in vitro and in PH rodents in vivo (Tables 1 and 2). Such experimental interrogation also revealed that actions of miR-21 in PH (28,(34)(35)(36) and elsewhere (22,83) are context specific and possibly cell specific. Thus, miR-21, while pleiotropic in its effects in PH, also carries a dynamic and shifting repertoire of actions that makes its functions as a consistent regulator of PH more challenging to define.…”
Section: Divergence Of Mirna Function Controlling Multiple Molecular mentioning
confidence: 99%
“…In turn, many of these miRNAs were confirmed to modulate PAH in vivo via use of antisense oligonucleotide inhibitor (antagomirs) (29,30). In addition, miR-21 processing is regulated by BMP signaling globally (31)(32)(33) and was shown to control PAH progression in vivo by genetic KO studies (28,34) and pharmacologic inhibition of miR-21 (35,36). Despite their modulatory activity in PH, however, actions of these miRNAs do not fully reverse disease manifestations, indicating a level of redundancy and actions as "fine tuners" consistent with their shared targeting of BMPR2.…”
Section: Cataloguing Mirnas Based On Their Convergent/divergent Functmentioning
confidence: 99%
“…Thus, it has been proposed that miR-21 has a dual effect on vascular function: over a short time, it protects against hypoxia and ischemia [70,[102][103][104], and over the longer term, leads to endothelial dysfunction, apoptosis [70,102,105,106], and eNOS dysfunction. The latter would occur by targeting the expression of antioxidant enzymes [70], as well as enhancing the levels of the endogenous eNOS inhibitor asymmetric dimethyl arginine (ADMA) by downregulating the expression of the enzyme dimethyl arginine dimethylaminohydrolase 1 (DDAH1) [105,107,108]. These data suggest that the dynamic regulation of miR-21 and miR-126 could participate in the early defense of the endothelium to hypoxia and oxidative stress; nonetheless, they prime endothelial dysfunction over the long term.…”
Section: Potential Role Of Hypoxia-induced Mirnas Mir-21 and Mir-126mentioning
confidence: 99%